Melatonin attenuates inflammatory response‐induced brain edema in early brain injury following a subarachnoid hemorrhage: a possible role for the regulation of pro‐inflammatory cytokines. Issue 3 (15th September 2014) - Chen, Jingyin; Chen, Gao; Li, Jianru; Qian, Cong; Mo, Hangbo; Gu, Chi; Yan, Feng; Yan, Wei; Wang, Lin
Abstract Melatonin is a strong anti‐oxidant that has beneficial effects against early brain injury (EBI) following a subarachnoid hemorrhage (SAH) in rats; protection includes the reduction of both mortality and neurological deficits. The molecular mechanisms underlying these clinical effects in the SAH model have not been clearly identified. This study examined the influence of melatonin on brain edema secondary to disruption of the blood–brain barrier (BBB) and the relationship between these effects and pro‐inflammatory cytokines in EBI following SAH using the filament perforation model of SAH in male Sprague–Dawley rats. Melatonin (150 mg/kg) or vehicle was given via an intraperitoneal injection 2 hr after SAH induction. Brain samples were extracted 24 hr after SAH. Melatonin treatment markedly attenuated brain edema secondary to BBB dysfunctions by preventing the disruption of tight junction protein expression (ZO‐1, occludin, and claudin‐5). Melatonin treatment also repressed cortical levels of pro‐inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α), which were increased in EBI 24 hr after SAH. To further identify the mechanism of this protection, we demonstrated that administration of melatonin attenuated matrix metallopeptidase 9 expression/activity and vascular endothelial growth factor expression, which are related to the inflammatory response and BBB disruption in EBI after SAH. Taken together, this report shows that melatonin prevents disruption of tight junction proteins which might play a role in attenuating brain edema secondary to BBB dysfunctions by repressing the inflammatory response in EBI after SAH, possibly associated with regulation of pro‐inflammatory cytokines.